The impact of different exercise modalities on chronic kidney disease: an umbrella review of meta-analyses - Correa, Hugo L.; Rosa, Thiago S.; Santos, Rafael L.; Mestrinho, Vitoria M.; Aquino, Thaís S.; Santos, Weberth O.; Neves, Rodrigo P.; Deus, Lysleine A.; Reis, Andrea L.; Barbosa, Jessica M.; Araujo, Thais B.; Verhoeff, Ruchama; et al. (Frontiers in Physiology, 2025)
IntroductionExercise is widely recognized for its benefits to chronic kidney disease (CKD) patients. However, the specific impact of different exercise modalities on CKD-related outcomes remains unclear. This study sought to summarize the effects of different exercise modalities on the main outcomes impacted by CKD.MethodsWe searched for systematic review with meta-analysis in PubMed, Embase, Web of Science, Scopus, and Cochrane databases. We evaluated the methodological quality of included studies by AMSTAR2 tool and by individually evaluating the heterogeneity, sample power, and statistical significances from meta-analyses.ResultsWe included 44 meta-analyses, encompassing 35,432 CKD patients in pre-dialysis and dialysis stages (peritoneal and hemodialysis). Data from meta-analyses with highly suggestive or strong evidence grading suggests that aerobic and combined training were most effective in improving cardiorespiratory fitness (main effect: 2.1, 95% CI: 0.8–3.4, and main effect: 3.4; 95% CI: 2.4–4.6, respectively). Combined training showed a consistent benefit in psychosocial domains (main effect: −7.3; 95% CI: −9.31 to −53). All exercise modalities significantly improve functional performance, except isometric training, which impacted just fistula maturation (main effect: 0.84; 95% CI: 0.5–1.2).ConclusionExercise emerges as a potential non-pharmacological therapy for CKD patients. Tailoring exercise to specific outcomes appears to be crucial, as different exercise modalities exhibit varying effectiveness.